Design and Build a Web-Based Service Information System at the Sejahtera Medika Clinic in Rangkasbitung - Jully Triansyah; Heti Heti; Rusma Insan Nurachim; Sandra Dewi Saraswati (The IJICS (International Journal of Informatics and Computer Science), 2021)
Clinic is a health service facility that provides individual health services providing basic or specific medical services, organized by more than one type of health and led by medical personnel. The service activities carried out are in the form of public services. So far, the service system at the Sejahtera Medika Clinic starts from patient registration, input patient data, diagnoses and prescribes, payments and reports data that still uses the manual method, namely bookkeeping using a ledger. This causes several obstacles that often hinder the clinical management, especially in obtaining data related to patient service information. For this reason, it is necessary to develop a system that utilizes computer technology with a guaranteed security system, then the data is stored in a database and stored automatically. The development method used in this research is the Waterfall method, where there are 5 stages, namely: Analysis, Design, Implementation, Testing and Maintenance. In the implementation using UML (Unified Modeling Language) tools including Use Case Diagrams, Activity Diagrams, Class Diagrams and Sequence Diagrams